Long-term effects of evolocumab in participants with HIV and dyslipidemia: results from the open-label extension period. (1st April 2022) - Boccara, Franck; Caramelli, Bruno; Calmy, Alexandra; Kumar, Princy; López, J. Antonio G.; Bray, Sarah; Cyrille, Marcoli; Rosenson, Robert S.
Abstract : Objectives: People with HIV (PWH) are at an increased risk of atherosclerotic cardiovascular disease. Suboptimal responses to statin therapy in PWH may result from antiretroviral therapies (ARTs). This open-label extension study aimed to evaluate the long-term safety and efficacy of evolocumab up to 52 weeks in PWH. Design: This final analysis of a multinational, placebo-controlled, double-blind, randomized phase 3 trial evaluated the effect of monthly subcutaneous evolocumab 420 mg on low-density lipoprotein cholesterol (LDL-C) during the open-label period (OLP) following 24 weeks of double-blind period in PWH with hypercholesterolemia/mixed dyslipidemia. All participants enrolled had elevated LDL-C or nonhigh-density lipoprotein cholesterol (non-HDL-C) and were on stable maximally tolerated statin and stable ART. Methods: Efficacy was assessed by percentage change from baseline in LDL–C, triglycerides, and atherogenic lipoproteins. Treatment-emergent adverse events (TEAEs) were examined. Results: Of the 467 participants randomized in the double-blind period, 451 (96.6%) received at least one dose of evolocumab during the OLP (mean age of 56.4 years, 82.5% male, mean duration with HIV of 17.4 years). By the end of the 52-week OLP, the overall mean (SD) percentage change in LDL-C from baseline was −57.8% (22.8%). Evolocumab also reduced triglycerides, atherogenic lipid parameters (non-HDL-C, apolipoprotein B, total cholesterol, very-low-density lipoprotein cholesterol, and lipoprotein[a]), and increased HDL-C. TEAEs were similar between placebo and evolocumab during the OLP. Conclusion: Long-term administration of evolocumab lowered LDL-C and non-HDL-C, allowing more PWH to achieve recommended lipid goals with no serious adverse events. Trail Registration: NCT02833844 Video abstract: http://links.lww.com/QAD/C441